Influence of torsion on the structure of machine elements made of polymeric materials by 3D printing - Dębski, Mariusz; Magniszewski, Marek; Bernaczek, Jacek; Przeszłowski, Łukasz; Gontarz, Małgorzata; Kiełbicki, Mateusz (Polimery, 2021)
In this work, on the example of a spline connection, the effect of 3D printing on the structure of machine elements made of polymeric materials after a torsion test was investigated. A clear influence of the type of polymer and the printing direction in the applied incremental technology [FFF (Fused Filament Fabrication) also known as FDM (Fused Deposition Modeling)] on the structure of the obtained elements was observed.